2018
DOI: 10.1016/j.ymthe.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Long Non-coding RNA 1 Promotes Metastasis and Chemo-Resistance of TSCC via the Wnt/β-Catenin Signaling Pathway

Abstract: Increasing evidence has shown that chemo-resistance is related to the process of epithelial-mesenchymal transition (EMT) and increased invasiveness by tongue squamous cell carcinoma (TSCC) cells. Long non-coding RNAs (lncRNAs) play pivotal roles in tumor metastasis and progression. However, the roles and mechanisms of lncRNAs in cisplatin-resistance-induced EMT and metastasis are not well understood. In this study, a chemotherapy-induced lncRNA 1 (CILA1) was discovered by using microarrays and was functionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…10,11 For example, lncRNAs HOTAIR, CYTOR, and SNHG14 participate in the metastatic cascade by regulating cell migration and invasion, [12][13][14] and lncRNAs ATB and CILA1 promote metastasis by inducing the epithelial-mesenchymal transition (EMT). 15,16 Our recent study discovered that lncRNA LBCS inhibits self-renewal and chemoresistance of BCa stem cells through the epigenetic silencing of SOX2. 17 Our previous study found that lncRNA BLACAT2 promoted BCa-associated lymphangiogenesis and lymphatic metastasis by enhancing vascular endothelial growth factor C (VEGF-C) signaling.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 For example, lncRNAs HOTAIR, CYTOR, and SNHG14 participate in the metastatic cascade by regulating cell migration and invasion, [12][13][14] and lncRNAs ATB and CILA1 promote metastasis by inducing the epithelial-mesenchymal transition (EMT). 15,16 Our recent study discovered that lncRNA LBCS inhibits self-renewal and chemoresistance of BCa stem cells through the epigenetic silencing of SOX2. 17 Our previous study found that lncRNA BLACAT2 promoted BCa-associated lymphangiogenesis and lymphatic metastasis by enhancing vascular endothelial growth factor C (VEGF-C) signaling.…”
Section: Introductionmentioning
confidence: 99%
“…At present, it has been found that many lncRNAs can be used as markers of TSCC. For example, lncRNA CILA1 could serve as a biomarker for the chemo-sensitivity of TSCC tumors [33] and LINC00152 could function as a biomarker for the early detection and prognosis prediction of TSCC [34]. Therefore, continuous exploration of lncRNA function might provide a more theoret ical basis for TSCC treatment.…”
Section: Tsccmentioning
confidence: 99%
“… 7 , 8 , 9 In recent years, with the deepening of cancer research, the mutation of non-coding genes, the change of epigenetic structures, and the change of genome structures can drive the generation of tumors. 10 , 11 , 12 , 13 From the point of view of gene expression and the regulation process, the gene expression and regulation of tumor cells are different from those of normal cells, so that they have the ability of infinite proliferation, even invasion and metastasis. 14 …”
Section: Main Textmentioning
confidence: 99%